Examining the Braiding and Weaving of Indigenous Ways of Knowing, Being, and Doing in Alberta Teacher Education - Danyluk, Patricia; Burns, Amy; Poitras Pratt, Yvonne; Kendrick, Astrid; Plante, Maureen; Wessel, Samara; Crawford, Kathryn; Lemaire, Eva; Hill, Joshua; Bright, Robin; et al. (Alberta Journal of Educational Research, 2023)
Alberta’s Teaching Quality Standard requires that all teachers possess and apply a foundational knowledge of Indigenous Peoples to their teaching. In 2020, representatives from ten Alberta teacher education programs came together to examine how they were braiding and weaving Indigenous ways of knowing, being, and doing into their programs. They also considered the challenges and successes encountered and the ways programs might work together to improve and combat anti-Indigenous racism. Drawing upon a collective case study methodology, representatives responsible for the design and delivery of Indigenous education within each of the programs completed an 18-question survey. Results demonstrate the Teaching Quality Standard (Alberta Education, 2018) served as a catalyst for deepening Indigenous ways of knowing, being and doing in preservice teacher training. The levels of integration are examined through the concept of differentiation (Tomlinson & Imbeau, 2010) and Kanu’s (2011) five levels of integration. Keywords: Indigenous ways of knowing, being and doing, teacher education programs, Teaching Quality Standard La norme de qualité pour l'enseignement de l'Alberta exige que tous les enseignants possèdent et appliquent une connaissance fondamentale des peuples autochtones dans leur enseignement. En 2020, des représentants de dix programmes de formation des enseignants de l'Alberta se sont réunis pour examiner la façon dont ils intègrent à leurs programmes les façons autochtones de savoir, d'être et de faire. Ils se sont également penchés sur les défis et les réussites rencontrés et sur les façons dont les programmes pourraient collaborer pour améliorer et combattre le racisme anti-autochtone. En s'appuyant sur une méthodologie d'étude de cas collective, les représentants responsables de la conception et de la prestation de l'éducation portant sur les autochtones dans chacun des programmes ont répondu à un sondage de 18 questions. Les résultats démontrent que la norme de qualité de l'enseignement (Alberta Education, 2018) a servi de catalyseur pour approfondir les façons autochtones de savoir, d'être et de faire dans la formation initiale des enseignants. Les niveaux d'intégration sont examinés à travers le concept de différenciation (Tomlinson et Imbeau, 2010) et les cinq niveaux d'intégration de Kanu (2011). Mots clés : Façons autochtones de savoir, d'être et de faire; programmes de formation des enseignants; norme de qualité pour l'enseignement